LTMaker: a tool for semiautomatic reconstruction of the embryonic lineage tree from 4D-microscopy - Vico-Vela, Francisco José; Lobo Fernández, Daniel; Gómez, Antonio; Burrezo García, Salvador; Fernández-Rodríguez, Jose David; Duloquin, L.; Maury, B.; Peyrieras, Nadine (My University, 2013)
Studies of animal development using a 4Dmicroscopy system generate an immense amount of image data. In order to properly analyze the recorded embryogenesis, a computer-aided systematic process of categorization of cells from the image data should be accomplished. We present a software tool named LTMaker for the systematic semiautomatic identification of embryonic cells centers and also to determine the underlying linage tree. The program saves the generated data to a file so that further analysis of the embryo can be performed with external tools.
Keywords: Morfogénesis; Biología computacional; Cell lineage trees; Assesment tool